The Relationship Between Cord Blood Cytokine Levels and Perinatal Characteristics and Bronchopulmonary Dysplasia: A Case–Control Study - Wang, Mengmeng; Luo, Chenghan; Shi, Zanyang; Cheng, Xinru; Lei, Mengyuan; Cao, Wenjun; Zhang, Jingdi; Ge, Jian; Song, Min; Ding, Wenqian; Zhang, Yixia; Zhao, Min; et al. (Frontiers in Pediatrics, 2022)
Objective To establish the association between serial levels of inflammatory cytokines in cord blood and perinatal characteristics and bronchopulmonary dysplasia (BPD) in preterm infants. Methods 147 premature infants with gestational age ≤32 weeks who were born and hospitalized in the First Affiliated Hospital of Zhengzhou University between July 2019 and August 2021 were enrolled in this retrospective case–control study. Multiple microsphere flow immunofluorescence was used to detect seven cytokines in cord blood collected within 24 h of birth. Demographics, delivery characteristics, maternal factors, neonatal characteristics, and clinical outcomes were collected for the two groups. An unconditional logistic regression model was used in this study to assess the clinical variables. Results IL-6 cord blood levels at birth were significantly higher in the BPD group than in the non-BPD group, but the odds ratio (OR) was very small (OR = 1). No differences in other cytokine concentrations were observed between the two groups. Multivariable logistic regression analysis demonstrated that increased maternal white blood cell (WBC) count on admission and lower birth weight increased the risk of BPD progression. Conclusions Increased IL-6 cord blood levels at birth in preterm infants may have trivial significance for predicting BPD. Furthermore, higher maternal WBC count on admission and lower birth weight increased the risk of BPD.